HEPATOPROTECTIVE THERAPY FOR LIVER DISEASES IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
It is shown that legalon is a rational hepatoprotective drug, which is recommended for use in children with liver diseases for preventive and therapeutic purposes.